Nanostructured Ni Based Anode and Cathode for Alkaline Water Electrolyzers - Fabrizio Ganci; Tracy Baguet; Giuseppe Aiello; Valentino Cusumano; Philippe Mandin; Carmelo Sunseri; Rosalinda Inguanta (Energies, 2019)
Owing to the progressive abandoning of the fossil fuels and the increase of atmospheric CO2 concentration, the use of renewable energies is strongly encouraged. The hydrogen economy provides a very interesting scenario. In fact, hydrogen is a valuable energy carrier and can act as a storage medium as well to balance the discontinuity of the renewable sources. In order to exploit the potential of hydrogen it must be made available in adequate quantities and at an affordable price. Both goals can be potentially achieved through the electrochemical water splitting, which is an environmentally friendly process as well as the electrons and water are the only reagents. However, these devices still require a lot of research to reduce costs and increase efficiency. An approach to improve their performance is based on nanostructured electrodes characterized by high electrocatalytic activity. In this work, we show that by using template electrosynthesis it is possible to fabricate Ni nanowires featuring a very high surface area. In particular, we found that water-alkaline electrolyzers with Ni nanowires electrodes covered by different electrocatalyst have good and stable performance at room temperature as well. Besides, the results concern nickel-cobalt nanowires electrodes for both hydrogen and oxygen evolution reaction will be presented and discussed. Finally, preliminary tests concerning the use of Ni foam differently functionalized will be shown. For each electrode, electrochemical and electrocatalytic tests aimed to establishing the performance of the electrolyzers were carried out. Long term amperostatic test carried out in aqueous solution of KOH will be reported as well.